2006
DOI: 10.1111/j.1460-9568.2006.04800.x
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and subcellular localization of neurokinin‐1 and neurokinin‐3 receptors in primate globus pallidus

Abstract: The primate globus pallidus receives massive innervations from GABAergic striatal neurons that co-release the neuropeptide substance P (SP). To expand our knowledge regarding SP interaction at pallidal level, we used single and double antigen retrieval methods to study the cellular and subcellular localization of SP and its high-affinity receptors neurokinin-1 (NK-1R) and neurokinin-3 (NK-3R) in the globus pallidus of the squirrel monkey (Saimiri sciureus). At the light microscopic level, a large number of neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 55 publications
1
9
0
Order By: Relevance
“…In SON and PVN, immunoreactivity for NK3-R observed with either confocal or electron microscopy has a clustered appearance in the neuronal nuclei (Howe et al, 2004; Haley and Flynn, 2006; Jensen et al, 2008). The nuclear immunoreactivity for NK3-R reported in globus pallidus and VTA has a similar clustered appearance (Levesque et al, 2006; Lessard et al, 2009). This clustered appearance is consistent with localization of NK3-R to nuclear suborganelles some of which are rich in histones (Handwerger and Gall, 2006; Misteli, 2007).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…In SON and PVN, immunoreactivity for NK3-R observed with either confocal or electron microscopy has a clustered appearance in the neuronal nuclei (Howe et al, 2004; Haley and Flynn, 2006; Jensen et al, 2008). The nuclear immunoreactivity for NK3-R reported in globus pallidus and VTA has a similar clustered appearance (Levesque et al, 2006; Lessard et al, 2009). This clustered appearance is consistent with localization of NK3-R to nuclear suborganelles some of which are rich in histones (Handwerger and Gall, 2006; Misteli, 2007).…”
Section: Discussionmentioning
confidence: 61%
“…Altered NK3-R expression occurs in a strain of hamsters with dystonia (Friedman et al, 2002), and a NK3-R antagonist reduces blood pressure in spontaneously hypertensive rats (Lessard et al, 2003). Nuclear NK3-R-IR has recently been shown ultrastructurally in globus pallidus and VTA neurons (Levesque et al, 2006; Lessard et al, 2009). In the current studies, NK3-R was detected in nuclear fractions from all brain areas examined.…”
Section: Discussionmentioning
confidence: 99%
“…Although the present focus is on the PVN, the same may apply to multiple other brain regions that express NK3R. Indeed, NK3R is detected within the nuclei of neurons in the globus pallidus and ventral tegmental area (40,41). Additional techniques were not used to identify whether nuclear NK3R in these brain areas associated with transcriptionally active chromatin, but the presence of the NK3R in nuclei of neurons in a variety of brain regions suggests that NK3R may affect gene activation under multiple conditions.…”
Section: Perspectives and Significancementioning
confidence: 88%
“…For example, under basal conditions, NK3R is found within the nucleus of neurons in the ventral tegmental area of rat (VTA) (40) and globus pallidus of squirrel monkeys (41). Limited NK3R is found in nuclei of SON neurons under basal conditions, but nuclear NK3R increases significantly in response to hypotension (26).…”
Section: Discussionmentioning
confidence: 99%
“…Much evidence indicated the expression of neurokinin‐1 receptor in globus pallidus (Mantyh et al ., 1984; Mounir & Parent, 2002; Levesque et al ., 2006). It has been reported that substance P‐positive fibers from the striatum are closely apposed to pallidal neurons that express neurokinin‐1 receptors (Mounir & Parent, 2002; Levesque et al ., 2003).…”
Section: Introductionmentioning
confidence: 99%